On Efficient Solutions to Multiple Objective Mathematical Programs - Lowe, T. J.; Thisse, J.-F.; Ward, J. E.; Wendell, R. E. (Management Science, 1984)
This note develops properties of quasi-efficient solutions and explores interrelationships to the classical concept of efficiency. In particular, a point is a quasi-efficient solution to a multiple objective mathematical program if and only if it is an optimal solution to a scalar maximum problem for some set of nonnegative weights on the objectives. This result is then used to characterize the set of quasi-efficient solutions as the union of efficient solutions to a multiple objective problem over all nonempty subsets of the objectives.